Perkawinan Semarga Menurut Hukum Adat Batak Toba (Studi Kasus Di Desa RiaRia, Kecamatan Pollung, Kabupaten Humbang Hasundutan, Sumatera Utara) - Tommy Christian Silalahi; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Marriage in the Toba Batak community is an inter-clan marriage. The process of exogamous marriage (marriage outside the clan group) is a characteristic of the marriage process of the Toba Batak community so that the Toba Batak community strictly prohibits the existence of semarga marriage because semarga marriage (Namariboto) is considered as incest.The research objective was to determine the concept of blood ties in the Toba Batak customary community with the concept of blood ties in general, as well as the legal consequences of the occurrence of same-clan marriages in the Toba Batak Indigenous community. This research is a type of empirical legal research that includes research on legal identification and research on legal effectiveness. The data collection technique used in this study was through interviews with Toba Batak traditional figures in Humbang Hasundutan, namely the Adat Leader in Humbang Hasundutan and using data documentation in the form of tarombo (silsilah Marga) in the Toba Batak Adat. Researchers used empirical legal research to see the conditions of the Toba Batak Indigenous people directly in terms of marriage. The results show that in the tradition of the Toba Batak community, which is a customary unit is a blood bond called the Marga.This clan functions as a sign of the brotherhood that exists between them. This relative relationship in the Toba Batak Indigenous community is generally referred to as the Dalihan Na Tolu system which clearly must be upheld by opening kinship with other families outside the blood ties caused by marriage. Semarga marriages in the Toba Batak Customs are taboo marriages in the prohibited marriage category. If this semarga marriage is carried out by the Toba Batak Indigenous people, it violates the customary rules so that they are called Na So Maradat (people who do not know the customs)Keywords: Toba Batak Customary Law, Toba Batak Traditional Marriage, Due to the same clan marriage